2015
DOI: 10.11144/javerianacali.ppsi13-1.bcdc
|View full text |Cite
|
Sign up to set email alerts
|

Bullying y cyberbulling: diferencias entre colegios públicos-privados y religiosos-laicos

Abstract: ResumenObjetivo. Analizar diferencias en el bullying presencial y el cyberbulling entre colegios públicos-privados y religiosos-laicos. Método. Participaron 3026 adolescentes y jóvenes del País Vasco (España), de 12 a 18 años (48.5% varones y 51.5% mujeres). Se administró el Test Cyberbullying (Garaigordobil, 2013) para evaluar el bullying cara a cara y el cyberbulling. El diseño de investigación fue descriptivo y comparativo de corte transversal. Resultados. Los resultados evidenciaron: (a) la cantidad de con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0
15

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 14 publications
1
7
0
15
Order By: Relevance
“…Moreover, part of the originality and contribution of this study comes from the age of the participants. A better understanding of the predictors and the mechanism of aggressive behavior among adolescents is relevant given the increase of negative affectivity, including depression and dissatisfaction during this stage of development (Angold et al, 2002;Goldbeck et al, 2007), and the elevated prevalence of aggressive manifestations in schools (Garaigordobil et al, 2015;Modecki et al, 2014). Our findings support that our 3-year SEL intervention focused on EI skills training was associated with lower negative affect, as well as decreased feelings of anger and hostility, and with a subsequent reduction in physical and verbal aggression.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…Moreover, part of the originality and contribution of this study comes from the age of the participants. A better understanding of the predictors and the mechanism of aggressive behavior among adolescents is relevant given the increase of negative affectivity, including depression and dissatisfaction during this stage of development (Angold et al, 2002;Goldbeck et al, 2007), and the elevated prevalence of aggressive manifestations in schools (Garaigordobil et al, 2015;Modecki et al, 2014). Our findings support that our 3-year SEL intervention focused on EI skills training was associated with lower negative affect, as well as decreased feelings of anger and hostility, and with a subsequent reduction in physical and verbal aggression.…”
Section: Discussionsupporting
confidence: 77%
“…What is more, the prevalence of aggressive manifestations in school contexts continues to be discouraging, especially when these aggressions become regular and involve power imbalance (see Modecki, Minchin, Harbaugh, Guerra, & Runions, 2014, for a recent review). This trend has also been a generalized phenomenon in Spanish academic environments, where the most frequent aggressive manifestation continues to be verbal aggression, with no distinction between type of school or context (Garaigordobil, Mart ınez-Valderrey, P aez, & Cardozo, 2015).…”
Section: Aggression Among Adolescentsmentioning
confidence: 99%
“…Abbotts, Williams, Sweeting and West (2004) found that youth who frequently attend mass were more likely to suffer from bullying. Along these lines, Garaigordobil, Martínez-Valderrey, Páez and Cardozo (2015) found that in the religious centers, there was more bullying and cyberbullying behavior than in the non-religious centers. However, other studies have not found significant relationships between the degree of religiousness and cyberbullying (Fu, Land & Lamb, 2013), thus more in depth studies are necessary on this variable.…”
Section: Discussionmentioning
confidence: 96%
“…Whereas some studies have found no differences in bullying between students of public and private schools (Garaigordobil, Martínez-Valderrey, Páez & Cardozo, 2015;García-Continente, Pérez & Nebot, 2010;Khamis, 2015), other studies have concluded that, in the few cases where differences were found, such as social or verbal exclusion, they were more frequent in private schools (Defensor del Pueblo, 2007;León, Felipe, Gómez & López, 2011). In contrast to these, the ISEI-IVEI (2012) report found a higher percentage of victims in public schools in the same direction as other international studies (Shujja, Att & Shujjat, 2014;Topçu, Erdur-Baker & Çapa-Aydin, 2008 and Torres-Cantero (2014) found no differences in victimization between students of public and private schools but it did find higher rates of aggressiveness in public schools in three out of eleven presential behaviours performed (slapping, fighting due to anger, hitting back at someone), and the opposite in a behaviour of verbal aggression (making fun of another person), which was more frequent in subsidized schools.…”
Section: Introductionmentioning
confidence: 98%